2002
DOI: 10.1002/lsm.10053
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between near‐infrared Raman spectroscopy and the histopathological analysis of atherosclerosis in human coronary arteries

Abstract: An algorithm using PCA and discriminant analysis based on m-distance has been developed and successfully applied to diagnose coronary artery disease by NIRS obtaining good sensitivity and specificity for each tissue category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 28 publications
3
90
0
2
Order By: Relevance
“…A widely used MVA method to analyze Raman spectra is PCA, because it is readily implemented in most standard software packages for data acquisition and data analysis. [32][33][34] A comprehensive review of PC analysis of Raman spectra can be found elsewhere. 35 PCA applies a set of linear-orthogonal transformations to the data set, which identifies correlated variables in the data and assigns them to new, uncorrelated variables, the socalled PCs.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…A widely used MVA method to analyze Raman spectra is PCA, because it is readily implemented in most standard software packages for data acquisition and data analysis. [32][33][34] A comprehensive review of PC analysis of Raman spectra can be found elsewhere. 35 PCA applies a set of linear-orthogonal transformations to the data set, which identifies correlated variables in the data and assigns them to new, uncorrelated variables, the socalled PCs.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…Few analytical methods satisfy this requirement and are sensible enough to study details of tissue compositions and structures. Among those methods, molecular vibrational spectroscopy is a potential technique to diagnose and study the evolution of human diseases, such as atherosclerosis [5] and precancerous and cancerous lesions [4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed as a tentative to correlate differences in the Raman spectrum to the tissue pathology [3][4][5][6][7][8][9][10][11]. FT-Raman have been used as a diagnostic in a variety of human diseases, mainly constructing a database and identifying main spectral features [8,15].…”
Section: Introductionmentioning
confidence: 99%
“…The first PCs are related to the larger variation of the data and the last PCs carry only noise [31]. Discriminant analysis is used to separate samples with similar characteristics into well-defined groups or classes.…”
Section: Introductionmentioning
confidence: 99%